1. Manometric Studies for Evaluation of Ano-Rectal Activity - Miyashita, Y.; Kikuoka, S.; Hiramoto, Y.; Ishihara, M.; Morita, K. (Nippon Daicho Komonbyo Gakkai Zasshi, 1977)
Quantitative anorectal manometry by open tipped method modified cylinder core was examined on 70 normal subjects ranging birth to adult for the evaluation of physiological anorectal function and also discussed the methodology of pressure studies. At the neonatal period, especially during first week of life, anorectal pressure is very low, as well as recto-sphincteric reflex shows inactive. However, greatest rate of growth takes place unti 2 months after birth. The length of anal canal develops markedly in the second decade. From the physiological point of view, we divided functional anal canal into 3 parts, ie, puborectalis zone, internal sphincter zone, external sphincter zone. With introduction of increasing volume of air into the rectal balloon, the internal sphincter zone showed gradual decrease of basal tone and the puborectalis zone a similar reduction of tonic activity. For the assesment of anorectal defecative motility, we advocate to measure the " REFLEX ANORECTAL PRESSURE PROFILE " which composed of projecting the pressure fall on the resting anorectal pressure profile. It demonstrates that the anorectum reduces its tone from upper part to downward with proportional to the increase of rectal pressure.